Autoantibodies Activating the β2-Adrenergic Receptor Characterize Patients With Primary and Secondary Glaucoma - Hohberger, Bettina; Kunze, Rudolf; Wallukat, Gerd; Kara, Katja; Mardin, Christian Y.; Lämmer, Robert; Schlötzer-Schrehardt, Ursula; Hosari, Sami; Horn, Folkert; Munoz, Luis; Herrmann, Martin (Frontiers in Immunology, 2019)
Recently, agonistic autoantibodies (agAAb) activating the β2 adrenergic receptor were detected in primary open-angle glaucoma (POAG) or ocular hypertension (OHT) patients and were linked to intraocular pressure (IOP) (Junemann et al., 2018). The aim of the present study was to quantify β2-agAAb in the sera of glaucoma suspects and patients with primary and secondary glaucoma. Patients with OHT (n=33), pre-perimetric POAG (pre-POAG; n=11), POAG (n=28), and 11 secondary OAG (SOAG) underwent ophthalmological examinations including examinations with Octopus G1 perimetry and morphometry. 25 healthy individuals served as controls. Serum-derived IgG samples were analysed for β2-agAAb using a functional bioassay. The beat-rate-increase of spontaneously beating cultured neonatal rat cardiomyocytes was monitored with 1.6 beats / 15 sec as cut-off. None of the sera of normal subjects showed β2-agAAb. In POAG or OHT patients increased beating rates of 4.1 ± 2.2 beats/15sec, and 3.7 ± 2.8 beats/15sec were detected (p>0.05). Glaucoma patients with (POAG) and without perimetric (pre-POAG) defects did not differ (pre-POAG 4.4 ± 2.6 beats/15sec, POAG 4.1 ± 2.0 beats/15 sec, p>0.05). Patients with SOAG yielded mean beating rates of 4.7 ± 1.7 beats/15sec (p>0.05). β2-agAAb were seen in 73% of OHT, 82% of pre-POAG, 82% of POAG, and 91% SOAG patients (p<0.001). Clinical data did not correlate with beating rate (p>0.05). The robust β2-agAAb seropositivity in patients with OHT, pre-POAG, POAG, and SOAG suggest a primary common role for β2-agAAb starting early in glaucoma pathophysiology and turned out to be an novel marker identifying all patients with increased IOP independent of glaucoma stage and entity.